STRATEGI NEGOSIASI DAN KONSEP KONTRAK PEMASARAN PADA KELOMPOK USAHA TEMPE DI MEDOKAN SEMAMPIR KOTA SURABAYA - Vieta Imelda C.; Dian Ferriswara; Agustiawan Djoko B (Universitas Ahmad Dahlan, 2021)
Medokan Semampir Surabaya has a tempe business group chaired by Mrs. Pujianti, where when she founded her business for the first time, the tempe industry was one of the household agro-industries with great potential to be developed. Constraints on agreements between entrepreneurs and buyers who are large entrepreneurs whose credit payment patterns make entrepreneurs afraid of not being paid, so there is a need for an appropriate agreement for the security of both parties, with assistance in writing letters by legal practitioners and law teachers to make the agreement safe. Promotional assistance in the form of digital marketing also makes sales increase to buyers outside of existing ones. The purpose of this community service is to make micro entrepreneurs understand and be familiar with the safe sale and purchase legal agreements for sellers and buyers and to start entering the virtual world for selling their tempe products. This community service methodology is by direct assistance to entrepreneurs to make sales agreements and create social media accounts for digital marketing. The results of this community service are in the form of a letter of agreement and a social media account for tempe entrepreneurs.